NFAT inhibitor tributylhexadecylphosphoniumbromide, ameliorates high fructose induced insulin resistance and nephropathy. (5th October 2015) - Sanghavi, Maitri; Vajir, Malek; Kumar, Sandeep; Tikoo, Kulbhushan
Abstract: High fructose diet (HFrD)-induced insulin resistance (IR) has been reported to be associated with an increase in albuminuria, glomerular hypertrophy and inflammation in kidney. However, the molecular mechanisms associated with high fructose-induced IR and renal dysfunction are still unclear. In the present study, we have investigated the role of nuclear factor of activated T-cell (NFAT) and its inhibitor, Tributylhexadecylphosphoniumbromide (THPB) in high fructose-induced IR and renal injury. NFAT inhibition by THPB treatment significantly improved HFrD-induced insulin resistance. Treatment with THPB markedly reduced high fructose diet-induced protein expression of NFATc4, PTEN and also alleviated expression of inflammatory markers in kidneys of HFrD rats. Further, THPB treatment not only improved acute ANG II responses but also repressed the processes of renal fibrosis, ECM accumulation, foot process effacement and renal apoptosis in HFrD rats. Taken together, we for the first time provide evidence that HFrD -induced insulin resistance and renal injury is associated with dysregulated NFATc4/PTEN signalling and THPB prevents this dysregulation through inhibition of NFATc4. Thus, targeting NFATc4 can be a novel therapeutic approach for preventing HFrD induced- IR and renal injury. Highlights: HFrD-induced IR and renal injury is associated with altered NFATc4/PTEN signalling. NFATc4 inhibition by THPB improves acute ANG II responses. NFAT inhibition by THPB represses the processes of renal fibrosis and inflammation. THPB also prevents foot process effacement and renal apoptosis in HFrD rats.